1981
DOI: 10.1159/000280407
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal Prostaglandins E<sub>2</sub> and F<sub>2</sub><sub>α</sub> in Experimental Renovascular Hypertension

Abstract: To study the role of renal prostaglandins (PGs) in renovascular hypertension, PGE2 and PGF2α concentrations in both inner and outer medullae of the kidney were measured by radioimmunoassay in rabbits with hypertension produced by left renal artery constriction. In the acute phase, a week after the surgery, PGE2 in the inner and outer medullae and PGF in the inner medulla were significantly increased in both the constricted and opposite kidneys (p < 0.01)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
1
7
1
Order By: Relevance
“…In our study split UPGE:V as a reflection of renal PGE2 synthesis [19], which is a factor in influencing renal sodium excretion [12], was investigated. In the early phase of 2K-1C RVH, it was reported that the synthesis of renal PGs is increased in the clipped kidney, which might be mediated by the reduction of perfusion pressure as well as increased local and circulating angiotensin II [13,18,20,21]. However, in the present study UPGE2V of the clipped kidney was significantly lower than the control value.…”
Section: Discussioncontrasting
confidence: 73%
“…In our study split UPGE:V as a reflection of renal PGE2 synthesis [19], which is a factor in influencing renal sodium excretion [12], was investigated. In the early phase of 2K-1C RVH, it was reported that the synthesis of renal PGs is increased in the clipped kidney, which might be mediated by the reduction of perfusion pressure as well as increased local and circulating angiotensin II [13,18,20,21]. However, in the present study UPGE2V of the clipped kidney was significantly lower than the control value.…”
Section: Discussioncontrasting
confidence: 73%
“…These data indicate that the ele vation of urinary PGE2 in the acute and intermediate phases may be a reasonable response to the elevated angiotensin II. However, as other reports suggested [5][6][7][8][9][10][11], the elevated renal PGE2 may partially act as a defensive factor for renal function and hypertension by promoting urinary sodium excretion.…”
Section: Discussionmentioning
confidence: 98%
“…There have been some studies on the course of twokidney, one-clip renovascular hypertension in dogs, rats, and rabbits [8,11,13,24,25]. Brown et al [11] divided the course of this hypertension into three phases: the initial acute phase, in which hypertension was mainly depend ent on angiotensin II, the second intermediate phase, in which the effect of angiotensin II was weakened and some other factors such as sodium retention and in creased arteriolar responsiveness to vasoconstrictors seemed to be involved, and the third maintenance phase, in which the role of angiotensin II was no longer obvious.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations